Modelling of heat transfer for progressive freeze concentration process by spiral finned crystallizer - Samsuri, S. (Chemical Industry Press, 2018)
This study presents a novel design for a spiral finned crystallizer which is the primary element of progressive freeze concentration (PFC) system, which simplifies the setup of the conventional system. After the crystallizer has been designed, the research experiments have been conducted and evaluated through a thorough analysis of its performance by developing a mathematical model that can be used to predict the productivity of ice crystal at a range of coolant temperature. The model is developed based on the basic heat transfer equation, and by considering the solution's and the coolant's convective heat transfer coefficient (h) under the forced flow condition. The model's accuracy is verified by making comparison between the ice crystal mass' experimental value and the values predicted by the model. Consequently, the study found that the model helps in enhancing the PFC system. Â© 2017 Elsevier B.V.